ЗОНАЛЬНЫЕ И РЕГИОНАЛЬНЫЕ ВИДЫ ОВРАГОВ - Любимов Б.П.; Ковалев С.Н. (My University, 2006)
Some specific types of gullies rise under different zonal and regional conditions. They differ by complex of morphological characteristics or by single one and by mechanism of formation. These types are as follow: 1) nival-thermoerosion (tundra zone), 2) suffusion-solifluction (forest zone), 3) typical erosion (steppe and forest-steppe), 4) scree-erosion and suffusion-erosion (arid zone), 5) karst-erosion (in the karst regions), 6) landslide-erosion (in the landslide regions), 7) suffusion-erosion (in the suffusion regions). The distinguishing of such zonal and regional types of gullies is necessary for their precise description and for improvement of models of their development and erosion-protection measures according to zones and regions.
Keywords: 551.4.435.162